2007
DOI: 10.1126/science.1145339
|View full text |Cite
|
Sign up to set email alerts
|

CHD1 Motor Protein Is Required for Deposition of Histone Variant H3.3 into Chromatin in Vivo

Abstract: The organization of chromatin affects all aspects of nuclear DNA metabolism in eukaryotes. H3.3 is an evolutionarily conserved histone variant and a key substrate for replication-independent chromatin assembly. Elimination of chromatin remodeling factor CHD1 in Drosophila embryos abolishes incorporation of H3.3 into the male pronucleus, renders the paternal genome unable to participate in zygotic mitoses, and leads to the development of haploid embryos. Furthermore, CHD1, but not ISWI, interacts with HIRA in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
238
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(249 citation statements)
references
References 17 publications
(36 reference statements)
5
238
3
Order By: Relevance
“…The consequence of binding is not clear. It has been demonstrated that CHD1 is required for the deposition of Histone H3.3 into chromatin in vivo and ubiquitination of histone H2B (80,81). CHD1 could in fact activate transcription rather than repress it.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of binding is not clear. It has been demonstrated that CHD1 is required for the deposition of Histone H3.3 into chromatin in vivo and ubiquitination of histone H2B (80,81). CHD1 could in fact activate transcription rather than repress it.…”
Section: Discussionmentioning
confidence: 99%
“…S1C). Unexpectedly, the expression of CHD1, another chromatin remodeling factor implicated in H3.3 deposition (10), was decreased at the onset of differentiation (Fig. 1B and Fig.…”
Section: Differential Expression Of Rc and Ri Components During Myoblastmentioning
confidence: 99%
“…As for nontranscriptional function, H3.3 or HIRA contributes to mammalian sex chromosome inactivation (7), germline cell development (8), and fertilization (9) through a massive genome-wide nucleosome assembly. Chromatin remodeling factor CHD1, which belongs to the chromodomain family of SNF2-like adenosine triphosphatases, is also responsible for H3.3 incorporation into the male pronucleus, presumably in couple with HIRA (10). Besides, HIRA is involved in the formation of senescence-associated heterochromatic foci (SAHF) (11) and the maintenance of gene silencing (12)(13)(14).…”
mentioning
confidence: 99%
“…The remodeling factor named chromodomain helicase DNA-binding protein 1 (CHD1) physically associates with HIRA to mediate massive H3.3 incorporation into male chromatin during the decondensation of the Drosophila sperm DNA upon fertilization ( Figure 3) [73]. Whether this chromatin-remodeling factor is required for other HIRA complex-mediated H3.3 depositions is an open issue.…”
Section: Additional Playersmentioning
confidence: 99%